2009
DOI: 10.1136/ard.2009.110593
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis: a risk factor for myocardial infarction?: Table 1

Abstract: These observations indicate that the prevalence of MI is increased in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 11 publications
5
45
2
4
Order By: Relevance
“…In 2006, Han et al found a moderate increase in the prevalence of IHD in AS patients from a US health insurance database, reporting a relative risk of 1.2 (95% CI 1.0-1.5) [23]. In another study, though specific to myocardial infarction (MI), Peters et al reported a strong association between AS and an increased prevalence of MI in Dutch females matched to the general population (5.75 (2.1 to 15.8)), but no association for males (1.60 (0.9 to 2.8)) [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Han et al found a moderate increase in the prevalence of IHD in AS patients from a US health insurance database, reporting a relative risk of 1.2 (95% CI 1.0-1.5) [23]. In another study, though specific to myocardial infarction (MI), Peters et al reported a strong association between AS and an increased prevalence of MI in Dutch females matched to the general population (5.75 (2.1 to 15.8)), but no association for males (1.60 (0.9 to 2.8)) [10].…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal primary care population from Wales, AS patients had similar rates of myocardial infarction (MI) and stroke as matched-controls, but hypertension was more prevalent [9]. A Dutch study found an increased prevalence of hypertension in patients with AS compared to the general population [6] and though a second Dutch study found female patients with AS to be at greater risk of developing myocardial infarction, male AS patients were not [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study showed an association between premature atherosclerosis and chronic inflammatory condition [8]. Patients with AS are at increased risk for developing coronary artery disease [9]. One study showed that the risk of cardiovascular events was increased by 30-50% in patients with AS [10].…”
Section: Discussionmentioning
confidence: 99%
“…Одна из основных причин леталь-ности при АС -ССЗ [17][18][19]. Так же как и при РА, ФР ССО при АС являются дислипидемия [20], повышенная распро-страненность АГ [17,21], СД 2-го типа [17], увеличение толщины комплекса интима -медиа или наличие АТБ [22][23][24]. Кроме того, отмечено увеличение частоты неате-росклеротических ССЗ (патология аортального клапана и нарушение проводимости).…”
Section: общие принципыunclassified